Review of the importance of aquatic prey for riparian arthropod predators - Middendorf, Franziska; Bundschuh, Mirco; Eitzinger, Bernhard; Entling, Martin H; Schirmel, Jens (Basic and applied ecology, 2025)
Aquatic-derived resources can be important subsidies for riparian consumers. We systematically reviewed variations in the use of aquatic prey by riparian predators and investigated whether changes and differences in the availability of emerging insects influence riparian arthropod predator communities. We found that aquatic subsidies present a major food source for several riparian arthropod predators. However, the role of aquatic prey in the diet varied between predator groups and hunting strategies. Riparian web-building spiders, especially horizontal web-builders such as Tetragnatha, showed the highest proportion of aquatic insects in their diet (70 %). However, free-hunting spiders and riparian beetles also benefited substantially from these subsidies. The use of aquatic prey decreased with increasing distance from the water, varied throughout the year in line with the emergence peaks, and was affected by habitat characteristics. Our review also shows that the abundance and biomass of riparian arthropod predators can be influenced by variations in the availability of aquatic subsidies. This was particularly evident for riparian web-building spiders, especially horizontal web-building spiders such as Tetragnatha. Despite the considerable research activity over the past two decades, we identified several research gaps and present opportunities for future studies. First, there is a clear geographical bias, with a marked lack of studies in the Southern Hemisphere and Asia, with the exception of Japan. Second, most studies have focused on a few families of mostly web-building spiders while only a few have considered spiders with different hunting modes (e.g., ambush hunters or free hunters on vegetation), carabids and other beetles. Third, most studies used stable isotope analysis (SIA) for prey analysis. Additional methods, such as polyunsaturated fatty acid (PUFA) analysis, molecular gut content analysis, or combinations of these methods with SIA, should give a clearer picture of the reliance of riparian arthropods on aquatic prey.